Gross anatomy and histology of the alimentary canal of Hierodula coarctata saussure (Mantodea: Mantidae) - Gaikwad, Sunil Madhukar; Patil, Aarati Nivasrao; Zende, Piyusha Rajendra (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2022)
The present study entails the description of the anatomy and histology of the alimentary canal of praying mantis, Hierodula coarctata Saussure (Mantodea: Mantidae), a predatory insect. The alimentary canal was isolated, processed and analysed anatomically and histologically by using stereomicroscope and light microscope. The alimentary canal of H. coarctata is classically divisible into foregut, midgut, and hindgut. The foregut has the pharynx, oesophagus, crop and proventriculus which has histological layers intima, epithelium, basement membrane and outer muscularia. The midgut is short with eight gastric caeca anteriorly has a single layer of columnar epithelial cells show merocrine secretion and nidi cell groups at regular intervals lined by lamellate peritrophic membrane internally and muscular coat externally. The hindgut consists of the ileum, colon, and rectum with histological layers viz. intima, epithelium, and muscles. The results of the present investigation revealed that the alimentary tract of the carnivorous insect H. coarctata was structurally and functionally adapted to digest and absorb protein-rich diet.